Twilight of Congress hegemony: emergence of bi-polar alliance system in Karnataka - Shastri, Sandeep (1999)
After its dismal performance in 1996, the Congress attempted to widen its support base among the OBCs and the minorities and is now projecting itself as the `natural' choice of the electorate. With the splitting of the Janata Dal, the state is likely to witness bi-polar contests between the BJP and its allies and the Congress. - Reproduced
Keywords: Elections - India - Karnataka; Elections